Influence of nonenzymatic posttranslational modifications on constitution, oligomerization and receptor binding of S100A12. - Kerstin Augner; Jutta Eichler; Wolfgang Utz; Monika Pischetsrieder (PLoS ONE)
This study examined the effect of methylglyoxal (MGO)-derived nonenzymatic posttranslational modifications (nePTMs) on the binding affinity of S100A12 to its natural receptor for advanced glycation end-products (RAGE). Binding of MGO-modified S100A12 to RAGE decreased significantly with increasing MGO concentration and incubation time. Ca(2+)-induced S100A12 hexamerization was impaired only at higher MGO concentrations indicating that the loss of affinity is not predominantly caused by disturbance of ligand oligomerization. nePTM mapping showed carboxyethylation of lysine (CEL) and the N-terminus without preferential modification sites. Besides, hydroimidazolone, hemiaminals, argpyrimidine, and tetrahydropyrimidine rapidly formed at R21. Even at the highest modification rate, hexamerization of synthesized CEL-S100A12 was unaffected and RAGE-binding only slightly impaired. Thus, nePTMs at R21 seem to be the major cause of MGO-induced impairment of S100A12 oligomerization and RAGE binding.